Systemic Racism in Canadian Higher Education: A Rapid Scoping Review of 22 Years of Literature - Cranston, Jerome; Bennett, Alexandria (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2024)
Although the ideals of higher education promote learning and personal growth irrespective of an individual’s social identity including their perceived or declared race, systemic racism continues to subject Indigenous, Black, and otherwise racialized students, staff, and faculty to unwelcoming academic cultures and, at times, hostilities. The aim of this rapid scoping review was to identify and analyze some of the available peer-reviewed, published research literature between 2000 and 2022 focused on systemic racism in the Canadian higher education context. The authors analyzed 32 articles included in the scoping review to identify the theoretical frameworks used to situate each study. In addition, the analysis surfaced concepts related to how systemic racism is structured and enacted. Using a thematic analysis, a narrative summary is also presented to describe the experiences of Indigenous and racialized staff, students, and faculty. This study offers insight to those committed to building healthier academic communities through understandings of systemic racism as it is theoretically framed, conceptualized, and experienced.